Recurrence in Toxoplasma Chorioretinitis: A Case Report: Poster Presentation - Case Report - Resident - Satyanegara, Pratistha; Helvinda, Weni (Majalah Oftalmologi Indonesia, 2023)
Introduction : Toxoplasma is the most common cause of chorioretinitis and recurrency of toxoplasma chorioretinitis often occur. Recurrences risk factors are patients above 40 years, patients with de novo toxoplasmosis lesions or with less than one year after the first episode, macular area involvement, lesions greater than one disc diameter, congenital toxoplasmosis, and bilateral compromise. Case Illustration : Female, twenty years old, complained blurred vision on the RE for two years. The patient had a history of cat contact and no systemic manifestation. Anterior segment examination in both eyes is normal with right eye visual acuity 1/60 and left eye visual acuity VA 6/6. Posterior segment examination on the left eye showed normal limit while the right eye showed hyperpigmentation in inferotemporal optic disc and nasal macula. Retina showed hard exudate. Macula showed yellow- white exudate with subretinal bleeding and macular star appearance. Foveal reflex under normal limit. Toxoplasma serology was IgG (+) and IgM (-). The patient has been treated with cotrimoxazole 2x960mg and methylprednisolone 1x32mg. Discussion : Visual acuity is severely damaged in recurrence toxoplasma chorioretinitis. There are several factors that affect the recurrences of toxoplasma chorioretinitis. In this patient, the risk factors found are de novo lesion, lesions greater than 1 disc diameter, and macular involvement. Cotrimoxazole can reduce recurrence in toxoplasma chorioretinitis but still recurrency can occur. Conclusion : Recurrences in toxoplasma chorioretinitis affect visual acuity, and even with adequate therapy, recurrence is possible.